(untitled) (Journal of the Bangladesh Agricultural University, 2017)
The study was carried out for the purpose of determining the drying kinetics as well as moisture sorption isotherm of hybrid-81 corn. Corn at about 31% moisture content (wb) was dried in a forced convective hot air cabinet dryer at different drying conditions, such as variable air dry bulb temperature (40°C, 50°C and 60°C) and loading density (3.56 kg/m2, 7.12 kg/m2, and 10.68 kg/m2) as well as in shining sun at different layers (3.56 kg/m2, 7.12 kg/m2, and 10.68 kg/m2). The water sorption isotherm of the dried corn was developed using vacuum desiccators, which contained saturated salt solutions in the range of 11-93% RHs. The mono-layer moisture content calculated by the Brunauer–Emmett–Teller (BET) model (6.76 g/100 g solid) was lesser than that calculated by the Guggenheim–Anderson–De Boer (GAB) model (10.53 g/100 g solid). The energy constants were 10.45 and 4.64 as per BET and GAB equation, respectively. Both models gave suitable fits for corn. The activation energy (Ea) for diffusion of water was found to be 11.09 kcal/gm-mole for corn. Furthermore, it was noticed that, with the increase of corn layer, the drying rate decreased in case of both sun and mechanical drying. However, higher loading density resulted in efficient drying, at least up to 10.7 kg/m2. It was shown that the drying time to obtain stability was the lowest for moisture content (12.08 %) corresponding to aw of 0.65 in case of BET or GAB monolayer moisture content. This finding could be helpful in predicting the storage life of corn. J. Bangladesh Agril. Univ. 15(2): 309-317, December 2017